The Influence of Motivation and Work Environment on the Performance of Generation Z Employees in South Jakarta - Diva Anastasya Karindra; Darto Darto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of motivation and work environment on the performance of Generation Z employees in the South Jakarta area. The problem identified in this study is the low performance of employees in several work sectors, which is suspected to be influenced by work motivation and work environment conditions. This study uses a quantitative approach with an associative design to measure the relationship between work motivation and work environment variables as independent variables, and employee performance as the dependent variable. Data were collected through questionnaires distributed to 100 respondents randomly selected using a random sampling method based on the Slovin formula. The results of the study indicate that work motivation has a positive and significant influence on employee performance, with a calculated t value of 2.354 (p = 0.021). In addition, the work environment is also proven to have a significant positive influence on employee performance, as evidenced by a calculated t value of 3.696 (p = 0.000). The conclusion of this study confirms that motivation and work environment play an important role in improving the performance of Generation Z employees. The practical implication of this study is the importance of managing motivation and optimizing the work environment to create a conducive work atmosphere that encourages productivity and the achievement of organizational goals.